The Effect of Foot Reflexology on Hospital Anxiety and Depression in Female Older Adults: a Randomized Controlled Trial - Bahrami, MScN, Tahereh; Rejeh, PhD, MScN, BScN, Nahid; Heravi-Karimooi, PhD, MScN, BScN, Majideh; Tadrisi, MScN, Seyed Davood; Vaismoradi, PhD, MScN, BScN, Mojtaba (International Journal of Therapeutic Massage & Bodywork, 2019)
Background: Patients with cardiovascular diseases usually suffer from hospital anxiety and depression. Aim: This study aimed to investigate the effect of foot reflexology massage on anxiety and depression in female older adults suffering from acute coronary syndrome. Participants: Ninety older women with acute coronary syndrome were randomly assigned into intervention and control groups (n=45 in each group). Research Design: A randomized controlled trial. Intervention: The intervention and control groups received foot reflexology massage and routine care, respectively. Main Outcomes Measures: The levels of anxiety and depression were evaluated using the hospital’s anxiety and depression scale (HADS) before and immediately after foot reflexology massage. Results: Foot reflexology massage reduced both anxiety (F(1.44)=19.11, p = .001) and depression (F(1.44)=16.76, p = .001) in acute coronary patients relative to control patients. The intervention had a large effect on hospital anxiety and depression. Conclusions: Foot reflexology massage is an efficient and safe intervention for alleviating psychological responses among female older adults suffering from acute coronary syndrome during hospitalization.